Collection and Surveillance: a legal-philosophical approach about Artificial Intelligence (Sociología y tecnociencia, 2021)
Applications based on artificial intelligence open up the concrete possibility of replicating in machines a reasoning ability similar to humans one, giving them the power to carry out non-programmed representations given that learning provided by algorithms and Big Data. The range of unavoidable dilemmas that the application of these systems raises in many areas of social life is overwhelming and the normative dimension of artificial intelligence is obviously one of the most delicate, due to the interests and principles involved. Some philosophical considerations on the relationships between law, politics and technological surveillance are raised here
Keywords: Artificial Intelligence; privacy, surveillance; prediction; bias.